Analisis Penerapan Akuntansi pada Usaha Alat Tulis Kantor di Alfapro Stationery (International Forum of Researchers and Lecturers, 2025)
This study analyzes the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) at Alfapro Stationery. The analysis results indicate that Alfapro Stationery has applied several basic principles of SAK EMKM in preparing its financial statements, such as recognizing fixed assets based on acquisition costs, recording inventory, and recognizing revenue and expenses. The financial statements prepared include the statement of financial position, income statement, and notes to the financial statements, supported by a computer-based accounting system (AIO System) that helps generate automatic financial reports every month, thereby increasing accuracy and transparency. However, Alfapro Stationery has not been able to separate personal and business assets, violating the